Functional analysis, diversity, and distribution of carbendazim hydrolases MheI and CbmA, responsible for the initial step in carbendazim degradation. (4th August 2022) - Zhang, Mingliang; Bai, Xuekun; Li, Qian; Zhang, Lu; Zhu, Qian; Gao, Siyuan; Ke, Zhijian; Jiang, Mingli; Hu, Junqiang; Qiu, Jiguo; Hong, Qing
Abstract: Strains Rhodococcus qingshengii djl‐6 and Rhodococcus jialingiae djl‐6‐2 both harbour the typical carbendazim degradation pathway with the hydrolysis of carbendazim to 2‐aminobenzimidazole (2‐AB) as the initial step. However, the enzymes involved in this process are still unknown. In this study, the previous reported carbendazim hydrolase MheI was found in strain djl‐6, but not in strain djl‐6‐2, then another carbendazim hydrolase CbmA was obtained by a four‐step purification strategy from strain djl‐6‐2. CbmA was classified as a member of the amidase signature superfamily with conserved catalytic site residues Ser157, Ser181, and Lys82, while MheI was classified as a member of the Abhydrolase superfamily with conserved catalytic site residues Ser77 and His224. The catalytic efficiency ( k cat / K m ) of MheI (24.0–27.9 μM −1 min −1 ) was 200 times more than that of CbmA (0.032–0.21 μM −1 min −1 ). The mheI gene (plasmid encoded) was highly conserved (>99% identity) in the strains from different bacterial genera and its plasmid encoded flanked by mobile genetic elements. The cmbA gene was highly conserved only in strains of the genus Rhodococcus and it was chromosomally encoded. Overall, the function, diversity, and distribution of carbendazim hydrolases MheI and CbmA will provide insights into the microbial degradation of carbendazim.